Analisa Efektivitas Waktu Manajemen Proyek Pada Pelaksanaan Pembangunan Gedung Pelayanan Terpadu Univeritas Tribhuwana Tunggadewi Malang - Salam , Moh. Hadits ; Suhudi ; Arifianto, Andy Kristafy (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2019)
The construction project of the Integrated Services Building of the University of Tribhuwana Tunggadewi in Malang City, East Java in 2019 which caused a slowing down in the duration of time due to the use of inappropriate scheduling methods. Therefore, in order to correct the slowing down of the time duration, it must use the correct and appropriate method, including the method that can be used, namely the CPM method. The use of the CPM method is desirable so that the project can be completed in a timely manner. Based on this, the research was carried out in order to find out the length of the duration of the construction project of the construction of the Integrated Services building of the tribhuwana Tunggadewi University of in Malang, East Java after using the CPM method and so that the duration could be known using the CPM method. The method of this research is carried out by using scheduling with M.S Project, accelerating activities that are on the critical path, re-analyzing the critical path to produce saturation time and produce optimum time. From the results of the study, it was found that the long duration of time obtained was 105 days from the normal time of 337 days or 232 days faster.